Reproducibility of the optic nerve head topography with a new laser tomographic scanning device - Rohrschneider, Klaus; Burk, Reinhard; Kruse, Friedrich E.; Völcker, Hans Eberhard (Ophthalmology, 1994)
Background: Laser scanning tomography has been shown to be an accurate and reliable method for the assessment of the three-dimensional optic disc topography. The authors investigate the reliability of morphometric measurements with the Heidelberg retina tomograph, a new instrument which was designed based on this technology, which simplifies handling and is much smaller than the laser tomographic scanner. Methods: Three independent measurements of the optic disc were performed in 39 eyes of 39 patients which were equally divided into the following three groups: glaucoma, glaucoma suspects, and controls. Results: The mean coefficient of variation for measurement in the glaucoma, glaucoma suspect, and control groups was 2.9%, 5.0%, and 3.4%, respectively, for cup area; 4.9%, 4.6%, and 4.6%, respectively, for cup volume; 5.2%, 3.8% and 3.3%, respectively, for mean cup depth; and 5.2%, 4.1 %, and 4.0%, respectively, for maximal cup depth. The mean standard deviation for one pixel of the total image was 30 ± 6 Jim, 28 ± 7 ,um, and 22 ± 6 ,urn for the three groups, respectively. Conclusion: The Heidelberg retina tomograph enables fast and reliable measurement of the optic disc topography and therefore may allow exact follow-up of patients.
Elektronische Reproduktion der Druck-Ausgabe 31. Oktober 2013
Gesehen am 08.07.2024